2020
DOI: 10.3390/ijms21072468
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin-Dependent Kinase Inhibitor Gene TaICK1 acts as a Potential Contributor to Wheat Male Sterility induced by a Chemical Hybridizing Agent

Abstract: Heterosis has been widely accepted as an effective strategy to increase yields in plant breeding. Notably, the chemical hybridization agent SQ-1 induces male sterility in wheat, representing a critical potential tool in hybrid seed production. However, the mechanisms underlying the male sterility induced by SQ-1 still remain poorly understood. In this study, a cyclin-dependent kinase inhibitor gene, TaICK1, which encodes a 229 amino acid protein, was identified as a potential contributor to male sterility in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…The stages of microspore development were identified by staining the anthers with 1% acetocarmine and 2% I 2 -KI. Samples were photographed using a DS-U2 high-resolution camera mounted on a Nikon ECLIPSE E600 fluorescence microscope (Nikon, ECLIPSE, E600, Tokyo, Japan) and analyzed using NIS-Elements software (Nikon, Tokyo, Japan) [ 12 , 82 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The stages of microspore development were identified by staining the anthers with 1% acetocarmine and 2% I 2 -KI. Samples were photographed using a DS-U2 high-resolution camera mounted on a Nikon ECLIPSE E600 fluorescence microscope (Nikon, ECLIPSE, E600, Tokyo, Japan) and analyzed using NIS-Elements software (Nikon, Tokyo, Japan) [ 12 , 82 ].…”
Section: Methodsmentioning
confidence: 99%
“…Heterosis refers to a phenomenon in which the F1 generation of genetically diverse individuals of the same species is superior to the parents in aspects such as yield, stress resistance, and adaptability [ 9 , 10 ]. Accordingly, the utilization of heterosis in wheat breeding represents one of the most effective strategies for improving the yield of this crop [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that abnormal division of microspore during gametogenesis can lead to male sterility, and abnormal division may be caused by abnormal microtubules [29]. Our previous studies found that meiosis and mitosis are abnormal in development of cytoplasm male sterile (CMS) lines in wheat [30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Wheat (Triticum aestivum L.) is one of the most important crops in the world, delivers around 20% of our food calories and protein, and feeds nearly 40% of the world's population [27,28].As the growth of the population and the changing of the global climate conditions, wheat breeding faces greater challenges. Heterosis utilization offered one of the most effective strategies for improving the yield and resisting the adverse natural environment [29]. Although cytoplasm male sterility is a much more effective in producing hybrid, the mechanisms of male sterile is still mystery.…”
Section: Introductionmentioning
confidence: 99%
“…There were two types of plant-specific CKI in land plants, known as Inhibitor/Interactor of CDC2 Kinase/KIP-related proteins (ICK/KRPs) and SIAMESE-related proteins (SMRs), of which SIM is the founding member. Among them, ICK/KRP members were reported to play diversity roles in root initiation, xylem pericycle development, pollen fertility, fruit enlargement and seed-setting (Brady 2019 ; Nafati et al 2011 ; Wen et al 2013 ; Yang et al 2011 ; Zhang et al 2020 ). The SMRs were identified later than ICK/KRPs and have limited studies over the past few years.…”
Section: Introductionmentioning
confidence: 99%